(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2024)
Social media is one of individual interactions between individuals in sharing and information exchanges. Social media can present the new communication. Magdalene uses Instagram as one of the platforms to tell and educate feminist issues. This research aims to acknowledge how is the utilization of social media as well as the type of feminist education which is given by Instagram account @Magdalaneid. This research uses qualitative description research method also using diffusion of innovation and feminist theory approach. Using collecting techniques data observation, interviews, and documentation. Data analysis model which is conducted is data collecting, data reduction, data presentation and drawing conclusion. The result of this research is Magdalene took Instagram to get more audience and optimize communication tools in social media, based on that, now followers of Instagram account @Magdaleneid gaining 107k followers. As a form of education given by Magdalene is to provide safe space for opinion exchanges with fearless judgment and also create educational content using feeds and reels feature on their Instagram account.